2013
DOI: 10.1002/2013gl058304
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Southern Ocean general circulation improved by animal‐borne instruments

Abstract: International audienceOver the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 20 publications
0
126
0
Order By: Relevance
“…This suggests that the bird-based wind estimates could be used to cover the satellite measurement gaps. In fact, geophysical data directly measured by instrumented animals or indirectly extracted from animal movements that complement conventional observation gaps have been assimilated to geophysical model analyses, as shown in currents extracted from shearwaters drift data (19) that were assimilated to ocean surface circulation models (20) and temperature and salinity profile measured by instrumented seals (11) used in Antarctic circumpolar circulation models (12). Wind stress and wind stress curl in coastal areas induce surface currents and upwelling systems that often generate areas of high biological productivity (6,8).…”
Section: Bird-based Wind Covers Spatial and Temporal Observation Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the bird-based wind estimates could be used to cover the satellite measurement gaps. In fact, geophysical data directly measured by instrumented animals or indirectly extracted from animal movements that complement conventional observation gaps have been assimilated to geophysical model analyses, as shown in currents extracted from shearwaters drift data (19) that were assimilated to ocean surface circulation models (20) and temperature and salinity profile measured by instrumented seals (11) used in Antarctic circumpolar circulation models (12). Wind stress and wind stress curl in coastal areas induce surface currents and upwelling systems that often generate areas of high biological productivity (6,8).…”
Section: Bird-based Wind Covers Spatial and Temporal Observation Gapsmentioning
confidence: 99%
“…For example, instrumented seals have been providing temperature and salinity profiles in the Antarctic Ocean for more than 10 y, especially under sea ice coverage that was difficult to measure by conventional methods (10,11). Adding these data to ocean circulation models improved the accuracy of estimated mixed layer properties (12). Bird-borne sensors are also used in measuring environmental variables such as temperature, depth, and light intensity directly from the instruments carried by the animal (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Reality intrudes in several ways. For example, (a) the interior circulation is a complex of various physics (Wunsch & Heimbach 2013, Gray & Riser 2014, Thomas et al 2014, (b) much of the fluid in the observed Gulf Stream enters from the Southern Hemisphere and ultimately derives from everywhere (e.g., Schmitz & Richardson 1991), and (c) fluid entering the deep western boundary current from the north is rapidly recycled into the interior long before it moves very far latitudinally (e.g., Lozier 1997). The first issue has been addressed by deploying instruments across the entire ocean width at the Florida Straits latitude (through a program called RAPID; Rayner et al 2011).…”
Section: Transport Choke Pointsmentioning
confidence: 99%
“…provides insight into the direct responses of individuals to their environment [38,53,54]. Since 2004, more than 270 000 CTD profiles were collected using CTD-SRDLs from SMRU (Sea Mammal Research Unit, St Andrews, Scotland) in the frame of SEaOS (Southern Elephant Seals as Oceanographic Samplers) and MEOP (Marine Mammal Exploration of the Oceans Pole to Pole; hooded, crabeater, Weddell and southern elephant seals) programs [55,56]. On average, two CTD profiles per day are transmitted and depending on the species the number of low-resolution dive profiles associated per day can be up to 15 more times (SES, Labrousse et al unpublished data).…”
Section: Ecological Applicationsmentioning
confidence: 99%